Reasons for Delaying Marriage By Japanese Women and its Impact and the Shoushika Phenomenon in the Japan Reporter Youtube Channel: Japan's Rise of Unmarried and Childless Women | Birthrate Crisis (EP.4) - Widhiutami, Bintang Satyaningwulan; Santoso, Budi (Journal La Sociale, 2025)
This study aims to analyze the causes and effects of marriage delay by Japanese women on the shoushika (low birthrate society) phenomenon as depicted in The Japan Reporter's YouTube video: "Japan's Rise of Unmarried and Childless Women | Birthrate Crisis (Ep.4)". This research employs a qualitative method to explore the factors influencing Japanese women's decisions regarding marriage and family, and their impact on Japan's declining birth rate. Findings from the content analysis and literature review indicate that changing social values, economic challenges, and difficulties in balancing work and personal life play significant roles in shaping Japanese women's perspectives and contribute to the shoushika phenomenon.